Mechanism of oil-solid interface adhesion in micro-scale flow within shale oil reservoirs - LIU Xiaoyu; HUANG Zhenkai; ZAN Ling; JIANG Zhigao; NIU Jun; LUN Zengmin (Youqi dizhi yu caishoulu)
This study focused on the mud shale reservoirs in the second Member of Funing Formation in Qintong Sag， Subei Basin of China， and systematically investigated the oil-solid interface adhesion mechanism of shale oil in micro-scale flow. Through detailed analysis of the mineral compositions， pore structures， and fluid characteristics of shale， the flow patterns of shale oil and the oil-solid interface adhesion mechanism in different types of shale were revealed by atomic force microscopy （AFM） and laser confocal microscopy. The findings indicate that shale oil in the reservoir exhibits distinct characteristics of selective production driven by pressure， whereby light components are preferentially adsorbed onto the shale walls， significantly enhancing the adhesion at the oil-solid interface. As pressure increases， heavy components start to flow， further augmenting the adhesion， but they stabilize once pressures exceed 5 MPa. Adhesion tests at the oil-solid interface demonstrate that laminated mudstone and massive silty mudstone emerge as key target shale types for enhancing shale oil recovery under low-pressure conditions. Under high-pressure conditions， the mechanism of adsorption and desorption of shale oil by laminated mudstone becomes the key research area for improving shale oil recovery in the second Member of Funing Formation in Qintong Sag.